Role of Psychological Capital in Increasing Positivity & Productivity in an Organization: The Impact of Psychological Capital on Positivity, Productivity, and Organizational Effectiveness (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As an additional objective, this article will investigate the role of positive psychologicalstrengths and capabilities in inspiring workers to go above and beyond the call of duty, which in turnboosts organizational effectiveness (PsyCap). A total of 297 individuals served as the sample. Pearson'scorrelation coefficient and multiple regression were used to examine the data. For this completeoperation, we utilised SPSS 21. Employee productivity was shown to be positively correlated with thevarious components of psychological capital (P0.001). The R2 value showed that 15 of productionvariance may be attributed to psychological capital.